O Pronaf no contexto do desenvolvimento rural sustentável da agricultura familiar no município de Maripá - Schultz, Claudio (2015)
The Agricultural and Cattle Raising Census of Family Farm 2006 by Brazilian Institute of Geography and Statistics IBGE shows that the family farm occupied 84.4% of agricultural and cattle raising establishments, but with only 24.3% of this area intended for agriculture. On the other hand, this kind of agriculture contributed expressively on food production being responsible for 87% of cassava national production, 70% of bean production, 46% of corn, 38% of coffee, 34% of rice, 21% of wheat and on animal production, 58% of milk, 59% of pig breeding, 50% of poultry and 30% of bovines, significative quantities on Brazilians market basket with a strategic support of credit lines from PRONAF. The aim of this research were identify the public polices existents relating to family farm sustainable development, understand about the modalities and involved resources on National Program for the Strengthening of Family Farming (PRONAF) that has a possibility of use in West of Paraná and confront with 2013/2014 agricultural plan; describing which modalities are more accessed in Maripá city and the demands of family farm that aren t contemplated in the program. So, also to know the PRONAF in a context of family farm sustainable development, in Maripá city, based on indicators of sustainability in their technical, social, economic, environmental and institutional policy dimensions. The research is presented in three papers that constitute the dissertation chapters: first, it was presented the theoretical context about agriculture history, sustainable rural development and public polices to support the family farm, in the second one, the contextualization of family farm in Maripá city, in the last one, the PRONAF in scope of family farm sustainable rural development in Maripá city. The qualitative and quantitative methodology was used based in a theoretical studies and structured interviews with 61 family farmers. After this, it was made a direct ponderation and used secondary elements. It could be concluded that the agriculture is a set of techniques, practices and social, that has as aim the animal and vegetal production, together with the concern about exploration and environmental impacts; that in Maripá city the family farm has its origin on agrarian model executed by Companhia Maripá on colonization of Britania s farm, whose model is maintained until nowadays and develops environmental practices that support the sustainable rural development; that there was a decrease of cultivated area, between 1993 and 2012; that the cultive of corn and soybean is indispensable, but with a considerable rise of dairy production, pig farming, poultry, fish farming and agricultural diversification; and that the familiar rural establishments has an 25,48ha average area, with diversification practices, exploration mainly by family, support from EMATER, credit available by PRONAF to costing and investment, which contributed to a rise of production, modernization and acquisition of new equipment, improvement of the infrastructure, agricultural expansion and diversification